1997
DOI: 10.1099/0022-1317-78-11-2837
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variation of the glycoprotein gene identifies three distinct lineages within field isolates of viral haemorrhagic septicaemia virus, a fish rhabdovirus.

Abstract: To evaluate the genetic diversity of viral haemorrhagic septicaemia virus (VHSV), the sequence of the glycoprotein genes (G) of 11 North American and European isolates were determined. Comparison with the G protein of representative members of the family Rhabdoviridae suggested that VHSV was a different virus species from infectious haemorrhagic necrosis virus (IHNV) and Hirame rhabdovirus (HIRRV). At a higher taxonomic level, VHSV, IHNV and HIRRV formed a group which was genetically closest to the genus Lyssa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
89
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 16 publications
(22 reference statements)
9
89
1
Order By: Relevance
“…We found that all French continental VHSV isolates belong to the same lineage, described as genotype I (Benmansour et al 1997) or genotype III (Stone et al 1997), grouping isolates from continental Europe. It is suggested that this group be designated 'Genotype I' since it contains the most ancient isolates.As already suggested (Benmansour et al 1997), subgroups could be distinguished within genotype I. The majority of the studied isolates are grouped in subgroups Ia or Ib.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…We found that all French continental VHSV isolates belong to the same lineage, described as genotype I (Benmansour et al 1997) or genotype III (Stone et al 1997), grouping isolates from continental Europe. It is suggested that this group be designated 'Genotype I' since it contains the most ancient isolates.As already suggested (Benmansour et al 1997), subgroups could be distinguished within genotype I. The majority of the studied isolates are grouped in subgroups Ia or Ib.…”
mentioning
confidence: 86%
“…For instance, a set of 13 isolates obtained between 1990 and 1996 had the same V2 sequence as isolate 3771 (sub-group Ib, Fig. 2).Only 1 isolate (L59X) was affiliated to genotype II, containing isolates from marine fish species such as Atlantic cod Gadus morhua (Stone et al 1997) or turbot Scophthalmus maximus (Benmansour et al 1997, Stone et al 1997. Interestingly, L59X was isolated from wild elvers Anguilla anguilla caught in the river Loire estuary (Castric et al 1992) showing that this migrating fish species can also be naturally infected by a VHSV strain of genotype II.…”
mentioning
confidence: 99%
See 3 more Smart Citations